(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
This article discusses the gradual stages of word adoption into the Uzbek language. In particular, structure and content of the words, such as garm, farsang, baxshish, daha were analyzed in terms of etymology and semantics